Procedure for the Preparation of Milligram Quantities of Adenovirus Messenger Ribonucleic Acid - Bhaduri, Saumya (1972)
Late after adenovirus 2 infection (18 hr), nearly all newly synthesized polysomal messenger ribonucleic acid (mRNA) is viral specified. Large amounts of adenovirus mRNA have been purified by utilizing membrane filtration at high ionic strength. With this procedure, molecules that contain polyadenylic acid [poly (A)] tracts are bound selectively, and ribosomal RNA can be separated from the viral mRNA which contains poly(A). Polysomal RNA synthesized 18 hr after infection was labeled in the presence of 0.02 μg of actinomycin D per ml and extracted at pH 9.0. This RNA annealed 40% to 3 μg of adenovirus 2 deoxyribonucleic acid; the RNA selected by membrane filtration bound 80% under the same conditions. The RNA eluted from membrane filters was 80 to 90% greater than 18S and contained species migrating as 31, 27, and 24S. Binding of polysomal RNA to individual membrane filters was linear, using as much as 300 μg of RNA per membrane. A 1.1-mg amount of viral RNA was prepared from 17.7 mg of polysomal RNA that had been purified by extraction at pH 9.0.